Pool of bovine morphogenetic proteins and guided tissue regeneration in the treatment of intrabony periodontal defects: I- Clinical measurements ''Pool'' de proteínas morfogenéticas bovinas no tratamento de defeitos periodontais intra-ósseos: I- Medidas clínicas - Maria do Carmo Machado Guimarães; Euloir Passanezi; Adriana Campos Passanezi Sant'Ana; Sebastião Luiz Aguiar Greghi (University of São Paulo, 2004)
The purpose of this study was to evaluate the effect of the pool of bovine BMPs on the treatment of intrabony defects. The sample comprised 15 patients aged 26 to 57 years old presenting with 10 pairs of lesions of 2 or 3 walls or 2-3 walls ³5mm, located in the same type teeth (premolar or molar) and same jaw. The test defects were treated with combination of a pool of bovine bone morphogenetic and resorbable hydroxyapatite carrier (BMPs- HA), bovine demineralized bone matrix (MB) and coverage by a bovine collagen barrier membrane. The control defects were treated with MB-HA and covered by a bovine collagen membrane. The clinical measurements at six months after therapy in the test group revealed a reduction in the mean probing pocket depth (PPD) of 1.63 ± 1.41mm (B) and 1.93 ± 0.96mm (L) and a mean change in the clinical attachment level (CAL) of 1.60 ± 1.16mm (B) and 1.46 ± 0.97mm (L). The control group showed a mean reduction of PPD of 1.93 ± 1.34mm (B) and 2.0 ± 1.51mm (L) and a mean change of CAL of 1.03 ± 1.24mm (B) and 1.30 ± 1.14 mm (L). The analysis of variance (ANOVA) demonstrated that the changes in the clinical parameters were statistically significant (p<0.05). There were no significant differences between the test and controls subjects (Student's test, p<0.005). These findings suggest that the use of a pool of bovine BMPs do not provide added effects to GTR in the treatment of intrabony defects. Este estudo teve como objetivo avaliar a aplicação do ''pool'' de BMPs bovinas no tratamento de defeitos intra-ósseos. A amostra constou de quinze indivíduos com idade entre 26 e 57 anos, apresentando um par de defeitos intra-ósseos comparáveis, localizados no mesmo arco em dentes do mesmo tipo (pré-molares ou molares) e com perda de inserção (PI) ³5mm. Em cada indivíduo, o defeito teste foi tratado com a associação ''pool'' de BMPs- carreador Hidroxiapatita reabsorvível (BMPs-HA), matriz orgânica bovina desmineralizada liofilizada (MO) e barreira de colágeno bovino, enquanto os defeitos controle foram tratados com MO-HA e barreira de colágeno. Na avaliação clínica aos seis meses após a medida inicial, o grupo teste apresentou variação de profundidade de sondagem (PS) de -1,63mm ± 1,141 na vestibular (V) e -1,93mm ± 0,961 na lingual (L) e variação do nível de inserção (NI) de -1,60mm ± 1,168 na V e -1,46mm ± 0,972 na L. O grupo controle apresentou variação de PS de -1,93mm ± 1,347 (V) e -2,0mm ± 1,511 (L) e variação de NI de -1,03mm ± 1,245 (V) e -1,30mm ± 1,114 (L). A análise de variância indicou que a variação de PS e NI foi significativa em ambos os grupos (p<0,05). Entretanto, de acordo com o teste t não houve diferença significativa entre os grupos quanto à variação PS e NI (p<0,05). Em conclusão, a aplicação do ''pool'' de BMPs não oferece benefícios adicionais ao tratamento de defeitos intra-ósseos.